Transient human auditory cortex activation during volitional attention shifting. - Christian Harm Uhlig; Alexander Gutschalk (PLoS ONE, 2017)
While strong activation of auditory cortex is generally found for exogenous orienting of attention, endogenous, intra-modal shifting of auditory attention has not yet been demonstrated to evoke transient activation of the auditory cortex. Here, we used fMRI to test if endogenous shifting of attention is also associated with transient activation of the auditory cortex. In contrast to previous studies, attention shifts were completely self-initiated and not cued by transient auditory or visual stimuli. Stimuli were two dichotic, continuous streams of tones, whose perceptual grouping was not ambiguous. Participants were instructed to continuously focus on one of the streams and switch between the two after a while, indicating the time and direction of each attentional shift by pressing one of two response buttons. The BOLD response around the time of the button presses revealed robust activation of the auditory cortex, along with activation of a distributed task network. To test if the transient auditory cortex activation was specifically related to auditory orienting, a self-paced motor task was added, where participants were instructed to ignore the auditory stimulation while they pressed the response buttons in alternation and at a similar pace. Results showed that attentional orienting produced stronger activity in auditory cortex, but auditory cortex activation was also observed for button presses without focused attention to the auditory stimulus. The response related to attention shifting was stronger contralateral to the side where attention was shifted to. Contralateral-dominant activation was also observed in dorsal parietal cortex areas, confirming previous observations for auditory attention shifting in studies that used auditory cues.